2019
DOI: 10.1038/s41467-019-10320-y
|View full text |Cite
|
Sign up to set email alerts
|

CD160 serves as a negative regulator of NKT cells in acute hepatic injury

Abstract: CD160 and BTLA both bind to herpes virus entry mediator. Although a negative regulatory function of BTLA in natural killer T (NKT) cell activation has been reported, whether CD160 is also involved is unclear. By analyzing CD160 −/− mice and mixed bone marrow chimeras, we show that CD160 is not essential for NKT cell development. However, CD160 −/− mice exhibit severe liver injury after in vivo challenge with α-galactosylceramide (α-GalCer). Moreover, CD160 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…For example, it is not surprising that intestine epithelial HVEM interacts mainly with CD160 expressed by intraepithelial lymphocytes (IEL), because these cells are in continual contact with the epithelium (Shui et al, 2012), and CD160 is the only HVEM binding partner IEL highly express. Reverse signaling by HVEM through either CD160 or BTLA could drive the biology in other instances, as reported recently for the germinal center response (Mintz et al, 2019) or in the liver inflammation model (Iwata et al, 2010;Kim et al, 2019;Miller et al, 2009). Ultimately, a deeper understanding of the biologic effects of HVEM may permit the safer use of muteins and other reagents in a therapeutic context; for example, in cancer immunotherapy, where soluble HVEM has shown benefit in a mouse model of lymphoma (Pasero and Olive, 2013;Sedy and Ramezani-Rad, 2019) or for treating inflammatory diseases.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…For example, it is not surprising that intestine epithelial HVEM interacts mainly with CD160 expressed by intraepithelial lymphocytes (IEL), because these cells are in continual contact with the epithelium (Shui et al, 2012), and CD160 is the only HVEM binding partner IEL highly express. Reverse signaling by HVEM through either CD160 or BTLA could drive the biology in other instances, as reported recently for the germinal center response (Mintz et al, 2019) or in the liver inflammation model (Iwata et al, 2010;Kim et al, 2019;Miller et al, 2009). Ultimately, a deeper understanding of the biologic effects of HVEM may permit the safer use of muteins and other reagents in a therapeutic context; for example, in cancer immunotherapy, where soluble HVEM has shown benefit in a mouse model of lymphoma (Pasero and Olive, 2013;Sedy and Ramezani-Rad, 2019) or for treating inflammatory diseases.…”
Section: Discussionmentioning
confidence: 54%
“…Similarly, liver inflammation was dependent on CD160 and/or BTLA interacting with HVEM. As suggested by other studies (Iwata et al, 2010;Kim et al, 2019;Miller et al, 2009), this behavior may be due to the loss of inhibitory signaling in the iNKT cells that initiate this inflammatory response. It was not greatly dependent on LIGHT binding to HVEM, suggesting LIGHT induced HVEM trimerization is not a major factor in promoting or inhibiting BTLA and CD160 signaling in this system.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…ConA-induced hepatitis in BTLA-or CD160-deficient mice is more aggressive than in WT mice, suggesting that BTLA and CD160 function as negative regulators of NKT cells. 12,13 In this same model, contrasting results have been reported in HVEM-deficient mice with either an increased or decreased liver pathology. One publication also showed increased susceptibility of HVEM-deficient mice to experimentally induced autoimmune encephalitis.…”
Section: Crossregulation and Bidirectional Signaling Of The Hvem-lighmentioning
confidence: 87%
“…CD160 is considered to be a marker of T cell depletion [40], while BTLA is structurally expressed by NKT cells as an inhibitory receptor that transmits signals from herpes virus entry mediator [41,42]. CD160 and BTLA share a common ligand that delivers inhibitory signals to NKT cells [43]. Our study revealed that HO-1/BMMSCs reduce IFN-γ expression in NKT cells by increasing their surface expression of co-inhibitory receptors, through which inhibitory signals are delivered to NKT cells, revealing a novel target for the regulation of NKT cell function.…”
Section: Discussionmentioning
confidence: 99%